Glaucoma and mortality risk: findings from a prospective population-based study - Kühn, Tilman; Rohrmann, Sabine; Karavasiloglou, Nena; Friedman, David S.; Cassidy, Aedin; Bärnighausen, Till; Schuster, Alexander K.; Nickels, Stefan (Scientific reports, 2021)
Glaucoma is a neurodegenerative disease with a structural change of the optic nerve head, leading to visual field defects and ultimately blindness. It has been proposed that glaucoma is associated with increased mortality, but previous studies had methodological limitations (selective study samples, lack of data on potential confounders, self-reported or secondary data on glaucoma diagnoses). We evaluated the association between diagnosed glaucoma and mortality in the population-based National Health and Nutrition Examination Survey (NHANES), a representative health survey in the United States. The survey cycles 2005-2006 and 2007-2008 included an extensive ophthalmic examination with fundus photography, which were used to derive standardized glaucoma diagnoses. Risk of all-cause mortality was assessed with multivariable Cox proportional hazards regression models accounting for the complex survey design of NHANES. Time to death was calculated from the examination date to date of death or December 31, 2015 whichever came first. 5385 participants (52.5% women) were eligible, of which 138 had glaucoma at baseline, and 833 died during follow-up. Participants with glaucoma were more likely to be older than those without glaucoma (mean age 69.9 vs. 56.0 years). Mean follow-up time was 8.4 years for participants with glaucoma, and 8.6 years for participants without glaucoma. Glaucoma was associated with increased mortality in an unadjusted Cox regression model (hazard ratio 2.06, 95% confidence interval 1.16 to 3.66), but the association was no longer statistically significant after adjusting for age and sex (hazard ratio 0.74, 95% confidence interval 0.46 to 1.17). Additional adjustment for a range of potential confounders did not significantly change the results. In this representative population-based study, we found no evidence of increased mortality risk in glaucoma patients.